Pengaruh Selulosa Nanokristal dari Serat Buah Kelapa Sawit sebagai Pengisi dan Kalium Klorida sebagai Agen Pendispersi Terhadap Sifat Fisik Bioplastik Berbasis Pati Biji Alpukat (Persea americana) - M. Thoriq Al Fath; Lubis, Maulida; Ayu, Ghendis Ekawati; Dalimunthe, Nisaul Fadilah (Talenta Publisher (Universitas Sumatera Utara), 2022)
This study aims to determine the effect of nanocrystalline cellulose and potassium chloride (KCl) to bioplastics from avocado seed starch and glycerol as plasticizer. In this study, nanocrystal cellulose obtained from palm fruit fiber was hydrolyzed using sulfuric acid (H2SO4) at a concentration of 50%. The starch used in this study was obtained from the avocado seed extraction process. On producing bioplastic, the casting method was used with the addition of nanocrystal cellulose as filler of 1%, 2%, 3%, and 4% (%w), KCl as dispersing agent of 0%, 1%, 2%, and 3% (%w), and glycerol as plasticizer by 30 (%w). Based on the density test, the optimum value was obtained at 2% of nanocrystal cellulose and 2% of KCl with the value around 0.041 gram/cm3. The best water absorption values were 57.1% and 53.8% which obtained at 2% of nanocrystal cellulose and 1% of KCl. Scanning Electron Microscope test results showed uniformly distributed nanocrystal cellulose granules filling the surface of the bioplastic. The addition of KCl as dispersion agent give a good impact.